Optimization of Idle Assets of the Ketapang Regency Government with the Highest And Best Use Method to Increase Local Original Income - Rosyadi, Rosyadi; Prislyawan, Prima Febria; Sulistiawati, Rini (International Journal of Social Service and Research, 2023)
Regional Original Revenue (PAD), which is a measuring tool in determining the ability of regions to finance the running of the wheels of government, must be strived to be improved in supporting services to the community. The strategy that can be done is to optimize the utilization of regionally owned assets. The financial capacity of the Ketapang Regency Government with PAD which is still below 10 percent reflects that the regional independence ratio is classified as "very low", so it still depends on the central government. This study aims to analyze the optimization of asset utilization, cooperation patterns and estimation of economic benefits obtained by local governments using the HBU method. This method is used to analyze the beneficial value of a vacant land with a physical, legal, financial and maximum productivity feasibility approach, to obtain the highest value and best use of a building investment plan. The results of this study are, alternative buildings that physically, legally, financially and maximum productivity meet the criteria in erecting buildings are for culinary centers, with a payback period (PP) of 5 years 8 months, NPV = 11,798,256,645, BCR = 1.70, IRR = 16.52% and maximum productivity of 58.71%. The utilization pattern that can be done is by the BGS mechanism with an estimated contribution of economic benefits of Rp. 31,221,117,200.00 in a period of time for 20 years